Modern methods of organic synthesis - Carruthers, W. (Cambridge: Cambridge University Press, 1978)
The third edition of this well-known textbook discusses some modern methods used in organic synthesis, and aims to show the value and scope of these methods and how they are used in the synthesis of complex molecules. The general plan of the book follows that of the second edition, but the opportunity has been taken to bring the book up to date and to take account of advances in knowledge and of new reactions which have come into use since publication of the earlier editions. Particular emphasis is placed on highly stereoselective organic chemistry, including stereoselective alkylations, aldol reactions, oxidations, epoxidations and reductions. New methods for the stereoselective formation of carbon-carbon double bonds, and modern application reactions are also fully considered. The book will be of use to students of chemistry and biochemistry at graduate and senior undergraduate level. It will also interest practising scientists in industry and research establishments who wish to familiarise themselves with modern synthetic methods.
Index 515-526p.
Keywords: Organic Chemistry; Chemistry